Clinical impact of angiotensin I converting enzyme polymorphisms in subjects with resistant hypertension - Imbalzano, Egidio; Vatrano, Marco; Quartuccio, Sebastiano; Di Stefano, Rossella; Aragona, Caterina Oriana; Mamone, Federica; D’Ascola, Angela; Scuruchi, Michele; Felice, Francesca; Trapani, Giovanni; Alibrandi, Angela; Ciconte, Vincenzo Antonio; et al. (Molecular and cellular biochemistry, 2017)
Angiotensin I converting enzyme ( ACE ) insertion/deletion (I/D) polymorphism is thought to affect renin–angiotensin system (RAS) activity and development of cardiovascular disease; significant associations between I/D polymorphism and atherosclerosis, stroke, nephropathy, and early mortality were already found. We investigated whether Southern Italy resistant hypertensives presented an association between the presence of I and/or D alleles and early vascular damage, inflammation, and insulin resistance. One-hundred-fifty resistant hypertensives were enrolled, studied, and genotyped; carotid intima-media thickness (cIMT), arterial stiffness (AS), and HOMA indices were also evaluated. D allele was more prevalent, and 74 patients presented DD homozygosis. Sixty-eight patients had metabolic syndrome (MetS), without significant differences between DD and I allele carriers. DD genotype appeared strongly associated with higher HOMA values (p < 0.001), and also with both Augmentation Index (AIx, p = 0.003) and Pulse Wave Velocity (PWV, p = 0.023). A significant association was found between DD genotype and cIMT (p < 0.005), while no association between ACE genotype and the presence of carotid plaques. HOMA was correlated with AS (PWV: p < 0.001; AIx: p < 0.01). DD genotype appeared to be associated with AS and HOMA index, but not with inflammation, independently from blood pressure values and the presence of other MetS factors, confirming D allele as an independent risk marker. Vascular damage may develop and progress independently from other risk factors in resistant hypertensives, likely through the interplay between ACE gene, RAS activity, and insulin resistance.